Is there a crack epidemic among students in Brazil?: comments on media and public health issues - Solange Aparecida Nappo; Zila M. Sanchez; Luciana Abeid Ribeiro
In the past year, the Brazilian Federal Government and society have reported and acted on a crack use epidemic, which has been exacerbated by the media. This study hypothesized that crack use has not increased at the rate suggested by the Brazilian media. A cross-sectional survey was carried out in 2010 usinga multistage probabilistic representative sample of Brazilian middle and high school students in the country's 27 state capitals. A total of 50,890 valid questionnaires were weighted, analyzed and results compared to the 2004 national school survey dataset. Considering lifetime and past year crack use, no change in consumption was found between 2004 and 2010. Official data in Brazil on middle and high school students does not support the assertion of a crack epidemic widely publicized by the media. Government measures to treat and prevent crack use are encouraged; however, the term epidemic has been inappropriately used to represent the static prevalence of crack consumption among students.